Cross-sectional study of lung cancer patients as a potential high-risk factor for abdominal aortic aneurysm - Hye Ran Gwon; A La Woo; Seung Hyun Yong; Young Mok Park; Song Yee Kim; Eun Young Kim; Ji Ye Jung; Young Ae Kang; Moo Suk Park; Du–Young Kang; Seong Yong Park; Sang Hoon Lee; et al. (PLoS ONE, 2025)
Background Abdominal aortic aneurysm (AAA) is more common in Non-small cell lung cancer (NSCLC) patients. Considering that ruptured AAA is potentially fatal, timely management of AAA would result in long-term survival benefits. We assess the prevalence and characteristics of AAA in resectable NSCLC patients who would benefit from AAA surveillance. Methods 1,019 resectable NSCLC patients in Severance and Kangbuk Samsung Hospitals were reviewed from January 2019 to November 2020. The control group comprised 2,899 cancer-free people who had a health check-up CT scan in Severance between January 2018 and December 2019. Results Among resectable primary NSCLC patients, 39/1,019 (3.8%; odds ratio [OR], 19.19; 95% confidence interval [CI], 8.10–46.46) had AAA compared with 6/2,899 (0.2%) in the control (P<0.001). In multivariable regression analysis, male (OR, 13.24; 95% CI, 1.50–117.48; P = 0.020), aging (OR, 1.10; 95% CI, 1.04–1.15; P<0.001), current smoker (OR, 4.20; 95% CI, 1.20–14.62; P = 0.024), and coronary artery disease (OR, 3.13; 95% CI, 1.48–6.62; P = 0.003) were independent risk factors for AAA in NSCLC. Conclusion The present study found that the incidence of AAA in resectable early-stage lung cancer patients was significantly higher than in the cancer-free control group. Therefore, we suggest that early-stage NSCLC patients, especially smokers older than 60 years, undergo regular AAA surveillance as part of their lung cancer monitoring.